The conformational and vibrational behavior of the inhibitory neuropeptide derived from beta-endorphin - Kecel Gündüz, Serda; Çelik, Sefa; Özel, Ayşen E.; AKYÜZ, SEVİM (Taylor & Francis Inc, 530 Walnut Street, Ste 850, Philadelphia, Pa 19106 USA, 2017)
In this study, conformational behavior, structural, and vibrational characterization of the carboxy terminal dipeptide of beta-endorphin (glycy-L-glutamine, glycyl-glutamine, beta-endorphin(30-31)), which is an inhibitory neuropeptide synthesized from beta-endorphin(1-31) in brain stem regions, has been investigated. The theoretically possible stable conformers were searched by means of molecular mechanics method to determine their energetically preferred conformations. The 360 different conformations were calculated with the phi, Psi, chi. dihedral angles using the Ramachandran maps. The most stable conformation of the title molecule is characterized by the extended backbone shape (e) in the BR conformational range with -.78 kcal/mol energy. The cis- and trans-dimeric forms of the dipeptide were also formed and energetically preferred conformations of dimers were investigated. The experimental methods (FT-IR, micro-Raman spectroscopies) coupled with quantum chemical calculations based on density functional theory (DFT) have been used to identify the geometrical, energetic, and vibrational characteristics of the dipeptide. The assignment of the vibrational spectra was performed based on the potential energy distribution of the vibrational modes. To investigate the electronic properties, such as nonlinear optical properties, the electric dipole moment, the mean polarizability, the mean first hyperpolarizability, and HOMO-LUMO energy gaps were computed using the DFT with the B3LYP/ 6-31++ G(d, p) basis set combination. The second-order interaction energies were derived from natural bonding orbital analysis. The focus of this study is to determine possible stable conformation on inhibitory neuropeptide and to investigate molecular geometry, molecular vibrations of monomeric and dimeric forms, and hydrogen bonding interactions of glycy-L-glutamine dipeptide.
Keywords: glycy-L-glutamine; beta-endorphin(30-31); inhibitory neuropeptide; vibrational spectra; Glycyl-Glutamine; Ab-Initio; Raman-Spectra; Force-Fields; Dipeptide; Hardness; Peptide; Glycine; Polarizability; Chemotherapy